Antiplatelet Therapy During Surgery: A Review - Bhuiyan, Golam Rahman; Habib, SM Ahsan; Anam, Md Khairul; Hussain, Ahmed Shafiqul; Islam, Md Shirajul; Haque, Mostasirul; Ahmed, Md Khurshed (University Heart Journal, 2012)
No abstract available DOI: http://dx.doi.org/10.3329/uhj.v7i2.10845 University Heart. Journal Vol. 7, No. 2, July 2011